(untitled) (REMUNOM, 2025)
He article "E-learning and Lesson Study in Teacher Training: Integrating Technology and Collaboration for Teacher Development" explores the intersection between distance learning and Lesson Study methodology as innovative strategies in teacher training. Through the integration of digital technologies, e-learning provides flexibility and accessibility to learning, allowing educators to develop skills continuously and autonomously. On the other hand, Lesson Study emphasizes collaboration between teachers, promoting joint reflection on pedagogical practices and the development of more effective classes. The study argues that the combination of these approaches can enrich teacher training, by fostering a collaborative learning environment, where educators can share experiences, discuss challenges and improve their teaching methodologies. The article also highlights the importance of institutional support and adequate technological infrastructure for the success of this integration, suggesting that continuous training should be a priority in educational policies. It is concluded that the union of e-learning and Lesson Study represents a valuable opportunity for the professional development of teachers, contributing to the improvement of educational quality.